Tracking of dietary patterns between pregnancy and 6 years post-pregnancy in a multiethnic Asian cohort: the Growing Up in Singapore Towards healthy Outcomes (GUSTO) study - Lee Y.Q. (Springer Science and Business Media Deutschland GmbH, 2023)
10.1007/s00394-021-02703-z